2020
DOI: 10.1049/el.2020.1386
|View full text |Cite
|
Sign up to set email alerts
|

Robust heart rate estimation from mobile face videos using an auto‐encoder

Abstract: Providing an easy‐to‐use and non‐invasive heart rate estimation system for home healthcare is imperative for detecting health deterioration in the early stages and for providing preventive treatments. To this end, we propose a ballistocardiographic method that estimates heart rate by analysing face videos and exploiting cyclic head motions caused by blood pumping through the carotid arteries during heartbeats. The proposed method addresses hand motion artefacts that occur while tracking head motions on a mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Previous research has demonstrated various methods for measuring pulse rate by applying independent component analysis (ICA), principal component analysis (PCA), fast Fourier transform (FFT), band pass filter (BPF) to RGB color data calculated in the region of interest (ROI) of facial images [ 1 , 7 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], and by analyzing head movement and blinking [ 12 , 14 , 35 ] under controlled laboratory conditions. However, in external environments (outdoor bench, car, drone), the pulse rate cannot be accurately measured due to factors such as the user’s fine body tremor, illumination changes, non-detection of the face, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated various methods for measuring pulse rate by applying independent component analysis (ICA), principal component analysis (PCA), fast Fourier transform (FFT), band pass filter (BPF) to RGB color data calculated in the region of interest (ROI) of facial images [ 1 , 7 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], and by analyzing head movement and blinking [ 12 , 14 , 35 ] under controlled laboratory conditions. However, in external environments (outdoor bench, car, drone), the pulse rate cannot be accurately measured due to factors such as the user’s fine body tremor, illumination changes, non-detection of the face, etc.…”
Section: Introductionmentioning
confidence: 99%